Waterfront City dengan Pendekatan Arsitektur Berkelanjutan Di Kota Parepare - Kurnia, Elvira Dewi; Rahayu, Irma; A’raaf Tauhid, Fahmyddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Pare-Pare City or commonly referred to as